Diverse Representations to The Sum of Powers of Two as a Means For Enhancing Interest and Creative Thinking in Mathematics Study - Dagan Miriam; Satianov Pavel; Teicher Mina (De Gruyter, 2021)
In this paper, we present several different approaches to formula for the sum of integer powers of two in accordance with different representations of this sum or different algebraic methods for its computation. Our long-term experience shows the effectiveness of discussion on this theme for enhancing interest and creative thinking of the students about solutions of various problems, not only in mathematics but also in others fields of knowledge.